Biosurfactant production by Bacillus subtilis using corn steep liquor as culture medium - Gudiña, Eduardo J.; Fernandes, Elisabete C.; Rodrigues, Ana I.; Teixeira, José A.; Rodrigues, Lígia R. (Frontiers in Microbiology, 2015)
In this work, biosurfactant production by Bacillus subtilis #573 was evaluated using corn steep liquor (CSL) as culture medium. The best results were obtained in a culture medium consisting of 10% (v/v) of CSL, with a biosurfactant production of about 1.3 g/l. To the best of our knowledge, this is the first report describing biosurfactant production by B. subtilis using CSL as culture medium. Subsequently, the effect of different metals (iron, manganese and magnesium) on biosurfactant production was evaluated using the medium CSL 10%. It was found that for all the metals tested, the biosurfactant production was increased (up to 4.1, 4.4 and 3.5 g/l for iron, manganese and magnesium, respectively). When the culture medium was supplemented with the optimum concentration of the three metals simultaneously, the biosurfactant production was increased up to 4.8 g/l. Furthermore, the biosurfactant exhibited a good performance in oil recovery assays when compared with chemical surfactants, which suggests its possible application in microbial enhanced oil recovery or bioremediation